Peran Informasi Akuntansi dalam Penentuan Keputusan Pembayaran Zakat Muzzaki - Evy Iskandar; Deddy Iskandar; Hafizh Maulana (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2019)
According to Research about the decision of zakat payment by compulsory zakat or muzakki in determining how much zakat to pay is very interesting to be traced as a muzakki behavior to fulfill his religious obligations. Muzakki's behavior towards zakat payment is inseparable from the explanation of some of the underlying reasons by looking at it from the perspective that leads to their understanding of religion or subjective norms, attitudes, and wills held by the muzakki. In terms of accounting it also relates to the accounting behavior of calculations and decisions that are the basis for muzakki's considerations. For this purpose, this study is to examine the behavior (compliance, attitudes and norms) of the decision to pay zakat and to find out whether accounting information mediates the relationship between behavior and the decision to pay zakat. This research was conducted on the perception of 100 muzakki people who pay zakat in all Baitul Mal in Aceh. Based on the results of the study, it was found that Muzakki's attitude had a positive and significant effect on the perception of zakat accounting information. The perception of accounting information has a positive and significant effect on the decision of muzaki to pay zakat through Baitul Mal. Accounting information only mediates the influence of attitudes on muzakki's decision to pay zakat but does not mediate subjective norms and muzakku's compliance to pay zakat. The study recommends the importance of accounting information to improve the decision of muzakki to pay zakat in Baitul Mal Aceh.